17O‐excess as a detector for co‐extracted organics in vapor analyses of plant isotope signatures. (10th July 2019) - Nehemy, Magali F.; Millar, Cody; Janzen, Kim; Gaj, Marcel; Pratt, Dyan L.; Laroque, Colin P.; McDonnell, Jeffrey J.
Abstract : Rationale: The stable isotope compositions of hydrogen and oxygen in water (δ 2 H and δ 18 O values) have been widely used to investigate plant water sources, but traditional isotopic measurements of plant waters are expensive and labor intensive. Recent work with direct vapor equilibration (DVE) on laser spectroscopy has shown potential to side step limitations imposed by traditional methods. Here, we evaluate DVE analysis of plants with a focus on spectral contamination introduced by organic compounds. We present 17 O‐excess as a way of quantifying organic compound interference in DVE. Methods: We performed isotopic analysis using the δ 2 H, δ 18 O and δ 17 O values of water on an Off‐Axis Integrated Cavity Output Spectroscopy (IWA‐45EP OA‐ICOS) instrument in vapor mode. We used a set of methanol (MeOH) and ethanol (EtOH) solutions to assess errors in isotope measurements. We evaluated how organic compounds affect the 17 O‐excess. DVE was used to measure the isotopic signatures in natural plant material from Pinus banksiana, Picea mariana, and Larix laricina, and soil from boreal forest for comparison with solutions. Results: The 17 O‐excess was sensitive to the presence of organic compounds in water. 17 O‐excess changed proportionally to the concentration of MeOH per volume of water, resulting in positive values, while EtOH solutions resulted in smaller changes in the 17 O‐excess. Soil samples did not show any spectral contamination. Plant samples were spectrally contaminated on the narrow‐band and were enriched in 1 H and 16 O compared with source water. L. laricina was the only species that did not show any evidence of spectral contamination. Xylem samples that were spectrally contaminated had positive 17 O‐excess values. Conclusions: 17 O‐excess can be a useful tool to identify spectral contamination and improve DVE plant and soil analysis in the laboratory and in situ . The 17 O‐excess flagged the presence of MeOH and EtOH. Adding measurement of δ 17 O values to traditional measurement of δ 2 H and δ 18 O values may shed new light on plant water analysis for source mixing dynamics using DVE.